The influence of packed cell volume versus plasma proteins on thromboelastographic variables in canine blood. Issue 4 (25th June 2020) - Lynch, Alex M.; Ruterbories, Laura; Jack, John; Motsinger‐Reif, Alison A.; Hanel, Rita
Abstract: Objective: Determine the correlation between kaolin‐activated thromboelastography (TEG) variables (R, K, angle, and maximum amplitude [MA]) and PCV, fibrinogen concentration (FC), and total fibrinogen (TF) in an ex vivo model. Animals: Two healthy adult mixed‐breed dogs. Procedures: Citrated whole blood was obtained and separated into packed red cells, platelet rich plasma, and platelet poor plasma (PPP). An aliquot of PPP was heated to denature heat labile proteins (fibrinogen, factor V, factor VIII). Blood components were recombined for analyses of 6 physiological scenarios: anemia with low fibrinogen; anemia with moderate fibrinogen; anemia with normal fibrinogen; anemia with normal saline; normal PCV and normal fibrinogen; and normal PCV and low fibrinogen. A Kruskal–Wallis test, along with linear regressions on pairwise combinations of TEG variables, was used to determine the correlation between TEG variables and PCV, FC, and TF. Results: Maximum amplitude correlated with FC ( R 2 0.60, P  < 0.001) and TF ( R 2 0.57, P  < 0.001) but not PCV ( R 2 0.003, P  = 0.7). Angle and K time were moderately correlated with FC ([angle: R 2 0.53, P  < 0.001]; [K: R 2 0.55, P  < 0.001]) and TF ([alpha angle: R 2 0.52, P  < 0.001]; [K: R 2 0.51, P  < 0.001]) but not PCV. The R time was weakly correlated with PCV ( R 2 0.15, P  < 0.009) but not FC or TF. Conclusions and clinical relevance: In an ex vivo model, plasma proteins but not PCV impacted TEG variables. This suggests that TEG changes noted with anemia are imparted by changes in available fibrinogen in a fixed microenvironment rather than artifact of anemia.